Emotions in Europe, 1517-1914.
1 online resource
Keywords: This volumeof primary sources focuses on the history of emotions in Europe and its empires between 1789 and 1914.The studyends with WW1, by which point psychology and modern frameworks for the self had become standard knowledge. The study examines the subjects of the self, family and community, religion, politics and law, science and philosophy, and art and culture. Sources include letters, diaries, legal papers, institutional records, newspapers, science and philosophical writings, literature and art from a diversity of voices and perspectives. Accompanied by extensive editorial commentary, this collection will be of great interest to students of history and literature.